2009
DOI: 10.1007/s11845-009-0400-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergency percutaneous transcatheter embolisation of acute arterial haemorrhage

Abstract: Emergency arterial embolisation is a potentially life-saving treatment. Although it is technically challenging, indications are becoming increasingly varied and outcomes are more successful because of the availability of microcatheters and effective embolisation materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Transarterial embolization is a less invasive and useful treatment for arterial bleeding . However, identification of extravasation by DSA alone is frequently difficult, especially in cases with relatively low‐level arterial bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transarterial embolization is a less invasive and useful treatment for arterial bleeding . However, identification of extravasation by DSA alone is frequently difficult, especially in cases with relatively low‐level arterial bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Transarterial embolization is a less invasive and useful treatment for arterial bleeding. 1,2,8,9 However, identification of extravasation by DSA alone is frequently difficult, especially in cases with relatively low-level arterial bleeding. Selective catheterization in the branches suspected of being responsible for bleeding may result in repeated DSA runs, the use of a large volume of contrast material, and an extended procedural time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital subtraction angiography‐guided interventional embolisation appears to be most useful in patients who do not respond to conservative treatment, those with high surgical risks or patients unlikely to tolerate bowel preparation and urgent colonoscopy . Treatment decisions for patients with LGIB are widely varied in the literature and are often based on local expertise and preference .…”
Section: Introductionmentioning
confidence: 99%
“…However, when DSA does not clearly display extravasation or pseudoaneurysm, particularly when only tumor staining is observed, there is no established consensus regarding the type of embolic material that should be utilized. In a recent study, it was reported that TAE with EmboSpheres for life-threatening hemorrhages in patients with gastric cancer [10,11], breast cancer [12] and neurofibroma [13] was safe and effective. Calibrated microspheres are able to access distal regions of the target arteries resulting in disappearance of tumor staining.…”
Section: Introductionmentioning
confidence: 99%